System Dynamics-Based Policy Design for Circular Economy: Achieving Sustainability Under SDG 12 - Aloysius Hari Kristianto; Lianto Lianto; Agustinus Kismet; Widyanto Widyanto; Ahmad Soleh (STKIP Singkawang, 2025)
The purpose of this study is to assess the impact of circular economy waste management implementation in Indonesia on environmental quality, public health, and long-term economic growth, as well as to provide policy options based on SDG 12. The System Dynamics technique involved modelling four subsystems: population, waste management, environmental contamination, and public health. Secondary data were gathered from SIPSN, BPS, and relevant literature and analysed using the Causal Loop Diagram (CLD), Stock Flow Diagram (SFD), and Mean Absolute Percentage Error (MAPE) accuracy validation. According to the simulation results, increasing the implementation of the 3R concept (Reduce, Reuse, Recycle) by 20% over 20 years (2011-2030) could reduce managed waste generation by 6.38 million tonnes per year, increase the GDP contribution of the waste management sector by 261.6%, and reduce air (62.04 Mg/L) and water (38.86 Mg/L) pollution. Furthermore, ARI and diarrhoea cases dropped by 74.8%. Model validation yielded a relatively low error rate (MAPE 2.39-14.44%), showing the model's dependability as a policy planning tool. The study's findings emphasise the significance of improving infrastructure (waste bank, MRF), integrating digital technologies, fostering multisector collaboration, and providing continual education. The findings lead to the creation of a system dynamics-based policy model for achieving SDG 12 through an inclusive circular economy strategy.